Design and implementation of novel encryption architecture using mix column with novel adder - Radha Appisetty; Munuswamy Siva Kumar (Indonesian Journal of Electrical Engineering and Computer Science, 2026)
Digital information is extremely simple to process these days, but it can be accessed by unauthorized people. Cryptography is one of the most effective and widely used methods for data security, to protect this information. The cryptography techniques are becoming popular and widely adopted due to the security threats during data transmission. An essential part of a cryptographic system, cryptography algorithms are developed and implemented to increase data security. The developers of these cryptographic algorithms took into consideration additional parameters, including speed, resource consumption, reliability, usage type, and flexibility, even if their primary goals are confidentiality, integrity, and authenticity. It’s important to understand that each component affects the way that a cryptographic technique is designed. Hence, this analysis presents the design and implementation of a novel encryption architecture using mix column with a novel adder. The novel encryption algorithm is designed for an encryption architecture (EA) with mix column using novel adder. This novel encryption algorithm will attain better security and performance.